COLONIZATION AND GROWTH OF FINANCIAL MARKETS IN AFRICA: AN INSTITUTIONAL APPROACH WITH INTERACTION EFFECTS - Bruno EMMANUEL ONGO NKOA; Charles CHRISTIAN ATANGANA ZAMBO; Franck MONDESIR TSASSA MBOUAYILA (Bankers, Markets & Investors, 2023)
This paper examines the interaction effect of settlement and institutions on the growth of African financial markets over the period 1996-2017. The data on colonization which comes from the pioneering work of Acemoglu et al. (2001) is decomposed into two samples including 29 for the settler mortality rate and 33 for the settler rate. Applying ordinary least squares (OLS) regression, we find that institutions exert a negative and significant influence on capital market growth in African countries where settler mortality rates were high while in countries where settlers settled, the interaction effect of settler sedentarization rate and institutions is positive and significant. These results remain robust to several tests conducted. As a key recommendation, we suggest that African governments put in place new institutional governance policies that take into account the current economic context to further improve the growth of their financial markets. JEL Classification: E44, F54, O43.